Rice Protein as an Alternative Ingredient for Sustainable Food Formulations: Nutritional Quality, Functional Properties, Health-promoting Potential, and Emerging Applications - Silvia Leticia Rivero Meza; Larissa Alves Rodrigues; Sonia Medina; Isabel Egea; Patricia Sinnecker; Mauricio de Oliveira (Plant Foods for Human Nutrition, 2026)
Abstract The growing demand for sustainable and nutritionally adequate protein sources has intensified interest in alternative plant proteins capable of supporting future food systems. However, many conventional plant proteins still present limitations related to allergenicity, digestibility, sensory quality, and functional performance, highlighting the need for novel sustainable ingredients. In this context, rice protein has emerged as a promising alternative due to its hypoallergenic nature, gluten-free composition, relatively high digestibility, suitability for specialized dietary applications, favorable techno-functional characteristics, and compatibility with sustainable food production systems. This review provides an integrated perspective on rice protein by critically discussing its nutritional quality, techno-functional properties, health-promoting potential, emerging food applications, and contribution to sustainable food systems, thereby addressing knowledge that has remained fragmented across previous reviews. Recent scientific studies addressing protein composition, digestibility, bioactive peptides, processing technologies, and applications in plant-based foods and nutraceutical systems were critically analyzed. Current evidence demonstrated that rice proteins and rice-derived peptides exhibit antioxidant, antihypertensive, anti-inflammatory, antidiabetic, and immunomodulatory activities, while recent advances in protein modification technologies have significantly improved solubility, emulsification, gelation, and structuring properties. Furthermore, the valorization of rice bran and broken rice supports circular economy strategies and sustainable food production. In this way, rice protein represents a strategic ingredient for the development of next-generation functional foods and sustainable health-oriented dietary systems.